ANALISIS FREKUENSI KEDATANGAN BUS TRANSJAKARTA DI WAKTU SIBUK DAN TIDAK SIBUK - Taniasi, Wizi Dewi; Wijaya, Hartono; Rackman, Susanto; Gunawan, Fergyanto E. (Industrial and Systems Engineering Assessment Journal (INASEA), 2012)
The high road traffic in Jakarta often leads to a massive traffic jam. The problem arises because the volume of vehicles increasing at a higher rate than the road development. To overcome the traffic jam problem, the government introduced bus rapid transit, known as TransJakarta, in 2004. They expects the users of the private vehicle will switch to using TransJakarta, which can further lessen the traffic congestion. However, until now, TransJakarta is still having a low ridership, and is not able to meet the expectation. Passengers often critize the system because of long inter-arrival time between buses, which forced passengers to wait for a long time. TransJakarta operator has to address this issue as quickly as possible before inhabitantsof Jakarta losing their trust on the system. In this study, we analyzed the arrival frequency of TransJakarta buses at the peak-period time and off-peak period time, and also analyzed the factors that affect the frequency.